Promoting Wives’ Rights From a Hadith Perspective - Anggraini, Rizki; ghifari, Muhammad; Ash, Abil (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2024)
In Islam, women have equal rights to those of men, albeit with certain differences in specific contexts. This research explores the impact of hadiths concerning women's rights as wives on the formation of contemporary Muslim identity. Employing a qualitative approach and library research methodology, this study collects and analyzes data from various secondary sources, including journals, tafsir (Quranic exegesis), and relevant hadiths. The analysis reveals several hadiths that has the matan that concerns to the rights of wives. Research findings indicate that these hadiths provide guidelines that support women's empowerment. The study emphasizes the significance of interpreting hadiths contextually to nurture dynamic and responsive female identities capable of addressing contemporary challenges.